Cloud native application protection platforms - Miles, Russ; Smith, Taylor; Giguere, Stephen (O'Reilly Media, Inc., 2024)
Cloud native security isn't a game for individual players. It requires team collaboration with a platform that can help cloud security engineers, developers, and operations people do their best work. That's what the cloud native application protection platform (CNAPP) delivers. With this practical guide, you'll learn how CNAPP can help you consolidate security through DevSecOps across cloud native technologies, practices, and application lifecycles. Through real-life attack scenarios, authors Russ Miles, Taylor Smith, and Steve Giguere help you explore how CNAPP not only mitigates multidimensional threats, but also reduces complexity and helps your team stay one step ahead of attackers. CNAPP provides a holistic approach to your cloud native development across identities, workloads, networks, and infrastructure.
Includes bibliographical references
Keywords: Cloud computing; Computer security; Infonuagique; Sécurité informatique